1994
DOI: 10.1007/bf02916820
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of cadmium, lead, selenium, and zinc in human blood and seminal plasma

Abstract: The concentrations of cadmium, lead, selenium, and zinc in blood and seminal plasma were determined in 76 Singapore males. Except for zinc, the concentrations were generally higher in blood than in seminal plasma (cadmium, 1.31 micrograms/L vs 0.61 micrograms/L; lead, 82.6 micrograms/L vs 12.4 micrograms/L, and selenium, 163.6 micrograms/L vs 71.5 micrograms/L). The mean concentration of zinc in seminal plasma was more than 30 times higher than in blood (202 mg/L vs 6.2 mg/L). Significant positive correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…When blood is added to BSK-II medium, RpoS-activated genes are induced (82). The high concentration of Zn 2ϩ relative to low concentration of Mn 2ϩ in human blood (which contains about 100 M Zn 2ϩ [90][91][92]) may account for this observation. Increased CO 2 has been shown to enhance BosR, RpoS, and OspC levels (83 lated by CO 2 , which further increases the level of BosR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When blood is added to BSK-II medium, RpoS-activated genes are induced (82). The high concentration of Zn 2ϩ relative to low concentration of Mn 2ϩ in human blood (which contains about 100 M Zn 2ϩ [90][91][92]) may account for this observation. Increased CO 2 has been shown to enhance BosR, RpoS, and OspC levels (83 lated by CO 2 , which further increases the level of BosR.…”
Section: Discussionmentioning
confidence: 99%
“…7). Given that human blood contains a high concentration of Zn 2ϩ relative to a low concentration of Mn 2ϩ (90)(91)(92), it is likely that the tick midgut during the feeding is under low Mn 2ϩ and high Zn 2ϩ conditions that favor the production of BosR and activation of the RpoS pathway. This model cannot explain the situation in the feeding larvae when spirochetes migrate from mammals to larval midguts, in which the RpoS pathway is not activated even in the presence of mammalian blood.…”
Section: Discussionmentioning
confidence: 99%
“…This was also shown by the research on blood cadmium level in a group of men in Singapore, where the mean cadmium level found was 1.31 mg/l (Xu et al, 1994). In Japan, a research conducted by Watanabe and associates showed that the mean cadmium level in blood of nonexposed women was 1.84 mg/l (Watanabe et al, 1996).…”
Section: Cadmium Levelsmentioning
confidence: 65%
“…33 Higher levels of Cd in WB compared to SP was associated with a significant decrease in sperm count, especially at a level higher than 1.5 μg/L. 34 In addition, a relation has been shown between lower levels of Cd in SP and low semen volume and sperm motility. 13 High levels of SP Cd was found to be associated with abnormal sperm parameters.…”
Section: Discussionmentioning
confidence: 98%